Characterization of the Complete Mitochondrial Genome of Basidiomycete Yeast Hannaella oryzae: Intron Evolution, Gene Rearrangement, and Its Phylogeny - Li, Qiang; Li, Lijiao; Feng, Huiyu; Tu, Wenying; Bao, Zhijie; Xiong, Chuan; Wang, Xu; Qing, Yuan; Huang, Wenli (Frontiers in Microbiology, 2021)
In this study, the mitogenome of H. oryzae was sequenced by NGS and successfully assembled. The H. oryzae mitogenome comprised circular DNA molecules with the total size of 26,444 bp. We found the mitogenome of H. oryzae partially deleted the tRNA gene transferring Cysteine. Comparative mitogenomic analyses showed that intronic regions were the main factors contributing to the size variation of mitogenomes in Tremellales. Introns of cox1 gene in Tremellales species were found to have undergone intron loss/gain events, and introns of H. oryzae cox1 gene may have different origins. Gene arrangement analysis revealed H. oryzae contained a unique gene order different from other Tremellales species. Phylogenetic analysis based on a combined mitochondrial gene set resulted in identical and well-supported topologies, wherein the H. oryzae was closely related to Tremella fuciformis. This study represents the first report of mitogenome for the Hannaella genus, which will allow further study of the population genetics, taxonomy, and evolutionary biology of this important phylloplane yeast and other related species.